2019
DOI: 10.1111/jvh.13105
|View full text |Cite
|
Sign up to set email alerts
|

Maternal HBsAg carriers and adverse pregnancy outcomes: A hospital‐based prospective cohort analysis

Abstract: Abbreviations: ALT, alanine transaminase; aOR, adjusting odds ratio; APOs, adverse pregnancy outcomes; BMI, body mass index; CI, confidence interval; DAGs, directed acyclic graphs;ELISA, enzyme-linked immunosorbent assay; FDR, false discovery rate; GDM, gestational diabetes mellitus; HBeAg, hepatitis B e antigen; HBsAg, Serum hepatitis B surface antigen; HBV, hepatitis B virus; HDP, hypertensive disorders of pregnancy; ICP, intrahepatic cholestasis pregnancy; LGA, large for gestational age; PROM, premature rup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
39
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 39 publications
(56 reference statements)
5
39
0
1
Order By: Relevance
“…Our results have demonstrated that in our obstetric population with an intermediate endemic city of 3.3% for HBV infection, HBV status did not exert any signi cant adverse effect on obstetric outcome. This was largely in line with studies conducted in western societies [8][9][10][11][12] and another in China [35], while the most recently reported prospective cohort study in China found only increased intrahepatic cholestasis, premature rupture of the membranes (but not PTB), and LGA infants [36]. Thus it appears that maternal chronic HBV infection would at most exert minimal or no adverse effects on pregnancy outcome, and at the same time even enhancing fetal growth which could manifest as reduced SGA [9,12] or increased…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Our results have demonstrated that in our obstetric population with an intermediate endemic city of 3.3% for HBV infection, HBV status did not exert any signi cant adverse effect on obstetric outcome. This was largely in line with studies conducted in western societies [8][9][10][11][12] and another in China [35], while the most recently reported prospective cohort study in China found only increased intrahepatic cholestasis, premature rupture of the membranes (but not PTB), and LGA infants [36]. Thus it appears that maternal chronic HBV infection would at most exert minimal or no adverse effects on pregnancy outcome, and at the same time even enhancing fetal growth which could manifest as reduced SGA [9,12] or increased…”
Section: Discussionsupporting
confidence: 85%
“…LGA and macrosomic infants [13][14][15]36]. Furthermore, there was a signi cant independent increase in spontaneous labor, which would in turn reduce the need for intervention such as labor induction.…”
Section: Discussionmentioning
confidence: 99%
“…Intrahepatic cholestasis of pregnancy is a common liver disease in pregnancy, with highly variable prevalence worldwide (0.3%–8.5%) 21,22 . ICP is diagnosed in women with gestational pruritus and increased serum levels of bile acids.…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies have demonstrated that HBV infection is not a cause of excessive maternal morbidity and mortality and has no effect on fetal growth restriction or preeclampsia rates, [ 18 20 ] other studies have found that HBV infection is associated with a higher incidence of adverse pregnancy outcomes, such as gestational diabetes mellitus, [ 21 ] hypertensive disorders of pregnancy, [ 22 ] preterm birth, [ 20 , 21 , 23 ] macrosomia, [ 22 ] and recently ICP. [ 24 26 ] However, unlike the former study, a prospective study by Cui et al found no significant difference in the incidence of ICP between pregnant women with and without HBV infection. [ 27 ]…”
Section: Introductionmentioning
confidence: 79%
“…[ 33 – 35 ] Recent studies have shown that HBV infection is associated with a higher incidence of ICP. [ 24 26 ] Tan et al discovered that pregnant women positive for HBsAg had a higher risk of intrahepatic cholestasis (age-adjusted OR 1.74; 95% CI 1.40–2.16) and surmised that hepatitis B increased the risk of ICP. [ 25 ] In a hospital-based prospective cohort study, Cai et al found that maternal HBsAg carrier status was associated with an increased risk of intrahepatic cholestasis pregnancy (age-adjusted OR 1.70; 95% CI 1.16–2.49); thus HBV infection during pregnancy may increase the risk of ICP.…”
Section: Discussionmentioning
confidence: 99%